Antiproliferative Role of Secondary Metabolites From Aspergillus unguis AG 1.1 (G) Isolated From Marine Macroalgae Enteromorpha sp. by Inducing Intracellular ROS Production and Mitochondrial Membrane Potential Loss Leading to Apoptosis - Sajna, Kuttuvan V.; Kamat, Siya; Jayabaskaran, C (Frontiers in Marine Science, 2020)
Drug resistance to the classically used chemotherapeutic drugs is the major challenge in their treatment of cancer needing the discovery of novel anticancer drugs. In terms of finding novel therapeutics, endophytes are quite promising as they are an excellent source of novel structures, which exhibit bioactivity. The present study demonstrated a dose-dependent antiproliferative activity of mycelial-derived secondary metabolites from a macroalgae associated endophyte Aspergillus unguis AG 1.1(G). The antiproliferative activity of A. unguis mycelial extract (AUME) was observed on different human cancer cell lines. PI live/dead assay further confirmed the cytotoxic potential of the mycelial extract. Furthermore, A. unguis mycelial extract caused mitochondrial membrane aberration and generated ROS production as well indicating its potential to induce cell death by apoptosis. The metabolic profiling of the mycelial extract using GC-MS and LC-MS/MS revealed the presence of fatty acids, a benzoquinolinone derivative, imidazolidinedione derivative, diethyl phthalate and phthalate acid ester, a difuraxanthone, two prenylxanthone analogues and a phthalide derivative and some unknown metabolites. Presence of 4-(4-Hydroxy-3,5-dimethoxy-phenyl)-3,4-dihydro-1H-benzo[h]quinolin-2-one, 1-hydroxy-3,5-dimethoxy-2-prenylxanthone, 1,6-dihydroxy-3-methoxy-2-prenylxanthone and 3-butylidene-7-hydroxyphthalide in AUME could be correlated to the notable cytotoxicity exhibited by the endophyte. The additional presence of many unidentified compounds heightened the prospects of finding some novel bioactive metabolites. Our results indicated that secondary metabolites produced by A. unguis AG 1.1 (G) have therapeutic potential as anticancer agents.